A Vibrio cholerae viral satellite maximizes its spread and inhibits phage by remodeling hijacked phage coat proteins into small capsids - Caroline M Boyd; Sundharraman Subramanian; Drew T Dunham; Kristin N Parent; Kimberley D Seed (eLife, 2024)
Phage satellites commonly remodel capsids they hijack from the phages they parasitize, but only a few mechanisms regulating the change in capsid size have been reported. Here, we investigated how a satellite from Vibrio cholerae, phage-inducible chromosomal island-like element (PLE), remodels the capsid it has been predicted to steal from the phage ICP1 (Netter et al., 2021). We identified that a PLE-encoded protein, TcaP, is both necessary and sufficient to form small capsids during ICP1 infection. Interestingly, we found that PLE is dependent on small capsids for efficient transduction of its genome, making it the first satellite to have this requirement. ICP1 isolates that escaped TcaP-mediated remodeling acquired substitutions in the coat protein, suggesting an interaction between these two proteins. With a procapsid-like particle (PLP) assembly platform in Escherichia coli, we demonstrated that TcaP is a bona fide scaffold that regulates the assembly of small capsids. Further, we studied the structure of PLE PLPs using cryogenic electron microscopy and found that TcaP is an external scaffold that is functionally and somewhat structurally similar to the external scaffold, Sid, encoded by the unrelated satellite P4 (Kizziah et al., 2020). Finally, we showed that TcaP is largely conserved across PLEs. Together, these data support a model in which TcaP directs the assembly of small capsids comprised of ICP1 coat proteins, which inhibits the complete packaging of the ICP1 genome and permits more efficient packaging of replicated PLE genomes.